2003
DOI: 10.1021/la035477d
|View full text |Cite
|
Sign up to set email alerts
|

Basic Hydrolysis of Crystal Violet in β-Cyclodextrin/Surfactant Mixed Systems

Abstract: The basic hydrolysis of crystal violet (CV) in mixed systems consisting of beta-cyclodextrin (beta-CD) and a micelle-forming surfactant, cetyltrimethylammonium chloride (CTACl), has been studied. beta-CD was found to catalyze the basic hydrolysis of CV through the interaction of its hydroxyl group, in its deprotonated form, with the carbocation in the complexed substrate. The addition of small amounts of CTACl, with [CTACl] below the critical micelle concentration, to beta-CD solutions does not have an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…The formation of host-guest complexes influences the kinetics of different reactions [28]. When the reaction rate decreases due to the presence of CDs, these can be used as stabilisers; however, of more interest are the situations in which CDs accelerate reactions or may even participate directly in guest hydrolysis [185,186].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of host-guest complexes influences the kinetics of different reactions [28]. When the reaction rate decreases due to the presence of CDs, these can be used as stabilisers; however, of more interest are the situations in which CDs accelerate reactions or may even participate directly in guest hydrolysis [185,186].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Garcia-Rio and coworkers have developed models that allow the computation of stability constants for CD-S host-guest association by measuring the rate constants of solvolysis of chemical probes, such as, crystal violet [28], 4-methoxybenzenesulfonil chloride [192], benzoyl chlorides [193], Nnitrososulfonamide [194] and m-nitrophenyl acetate [195].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The insert of Fig. 5 presents the values of the binding constants of MNTS [28,37,[39][40][41] and CV [42,52] for different normal micelles as a function of the chain length of the surfactant. Taking into account these ratios, and assuming that the binding constant of CV [15] for OTACl and 45 times bigger than the ratio of SDS.…”
Section: Resultsmentioning
confidence: 99%
“…When the added amounts of QDs were higher than this concentration, the value of ΔF began to decrease. From the reported experimental data with HNMR and theoretical calculation results [26,27], one crystal violet molecule, which has very similar chemical structure to MG, was introduced into one β-CD molecule through its wide opening and one complete phenyl group was accommodated within its interior, the stoichiometry of the complex is 1:1. Our study in the present work also confirmed that the stoichiometry of the complex β-CD-MG is 1:1.…”
Section: Effects On the Fluorescence Intensity Of Ome-β-cd/qdsmentioning
confidence: 99%